Effector memory CD4+ T cells differentially express activation associated molecules depending on the duration of American cutaneous leishmaniasis lesions. (6th June 2016) - de Oliveira Mendes‐Aguiar, C.; Vieira‐Gonçalves, R.; Guimarães, L. H.; de Oliveira‐Neto, M. P.; Carvalho, E. M.; Da‐Cruz, A. M.
Summary: A high number of Leishmania ‐responder T cells is found in cutaneous leishmaniasis lesions, suggesting that important immunological events occur at the site of infection. Although activated, cytotoxic and regulatory T cells infiltrating into lesions may influence disease pathogenesis, the role of the T cell differentiation pattern of lymphocytes in lesions is unknown. Our aim was to investigate whether the phase of lesion development (early or late) is influenced by the functional status of cells present in inflammatory infiltrate. Activation, cytotoxity and T cell differentiation molecules were evaluated in lesion mononuclear cells by flow cytometry. The frequency of T cells was correlated with the lesion area ( r  = 0·68; P  = 0·020). CD4 + CD25 + T cells predominated over CD4 + CD69 + T cells in early lesions (less than 30 days), whereas late lesions (more than 60 days) exhibited more CD4 + CD69 + T cells than CD4 + CD25 + T cells. The duration of illness was correlated positively with CD4 + CD69 + ( r  = 0·68; P  = 0·005) and negatively with CD4 + CD25 + T cells ( r  = −0·45; P  = 0·046). Most CD8 + T cells expressed cytotoxic‐associated molecules (CD244 + ), and the percentages were correlated with the lesion area ( r  = 0·52; P  = 0·04). Both CD4 + and CD8 + effector memory T cells (TEM ‐CD45RO + CCR7 – ) predominated in CL lesions and were significantly higher than central memory (TCM ‐CD45RO + CCR7 + ) or naive T cells (CD45RO – CCR7 + ). An enrichment of TEM cells and contraction of naive T cells were observed in lesions in comparison to blood ( P  = 0·006) for both CD4 + and CD8 + T cells. Lesion chronicity is associated with a shift in activation phenotype. The enrichment of TEM and activated cytotoxic cells can contribute to immune‐mediated tissue damage.